2016
DOI: 10.1038/srep35545
|View full text |Cite
|
Sign up to set email alerts
|

Independent Long Fingers are not Essential for a Grasping Hand

Abstract: The human hand is a complex integrated system with motor and sensory components that provides individuals with high functionality and elegant behaviour. In direct connection with the brain, the hand is capable of performing countless actions ranging from fine digit manipulation to the handling of heavy objects. However the question of which movements mostly contribute to the manipulation skills of the hand, and thus should be included in prosthetic hands, is yet to be answered. Building from our previous work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
(64 reference statements)
2
15
0
2
Order By: Relevance
“…Finger abduction/adduction fails to show either a strong coordination or group coupling with other joint movements (sections ''Coordinated joint movements'' and ''Determining the minimum number of DoAs''), which may indicate that adduction movements need to be included in anthropomorphic hand design. This finding is also consistent with the overall findings of Montagnani et al, 19 which suggest that independent abduction/adduction of hand fingers have a significant role in grasping skills. In addition, some prosthetic hands neglect finger DIP joints.…”
Section: Resultssupporting
confidence: 92%
“…Finger abduction/adduction fails to show either a strong coordination or group coupling with other joint movements (sections ''Coordinated joint movements'' and ''Determining the minimum number of DoAs''), which may indicate that adduction movements need to be included in anthropomorphic hand design. This finding is also consistent with the overall findings of Montagnani et al, 19 which suggest that independent abduction/adduction of hand fingers have a significant role in grasping skills. In addition, some prosthetic hands neglect finger DIP joints.…”
Section: Resultssupporting
confidence: 92%
“…The finger mechanism requires an accurately controlled input force of 30 N per finger. To provide dexterity but maintain a compact and lightweight mechanical design, we decided to couple the motion of all fingers except for the thumb as suggested in [27]. Consequently, the needed force adds up to a total of 120 N for the four coupled fingers.…”
Section: A Application-specific Requirementsmentioning
confidence: 99%
“…We demonstrated that by taking advantage of compliance in the design of hand exoskeletons, the number of essential target hand poses can be reduced, resulting in easier and more robust control of the device in real-time. Grasping skills mainly rely on independent abduction/adduction of the thumb and flexion/extension of the thumb and fingers (Tavakoli et al, 2015;Montagnani et al, 2016). Therefore, optimizing the number of target poses is a crucial component for an sEMG-driven hand orthosis.…”
Section: Emg-driven Maestro Controlmentioning
confidence: 99%